Chemotherapy and Physical Therapeutics Modulate Antigens on Cancer Cells - Szlasa, Wojciech; Janicka, Natalia; Sauer, Natalia; Michel, Olga; Nowak, Bernadetta; Saczko, Jolanta; Kulbacka, Julita (Frontiers in Immunology, 2022)
Cancer cells possess specific properties, such as multidrug resistance or unlimited proliferation potential, due to the presence of specific proteins on their cell membranes. The release of proliferation-related proteins from the membrane can evoke a loss of adaptive ability in cancer cells and thus enhance the effects of anticancer therapy. The upregulation of cancer-specific membrane antigens results in a better outcome of immunotherapy. Moreover, cytotoxic T-cells may also become more effective when stimulated ex-vivo toward the anticancer response. Therefore, the modulation of membrane proteins may serve as an interesting attempt in anticancer therapy. The presence of membrane antigens relies on various physical factors such as temperature, exposure to radiation, or drugs. Therefore, changing the tumor microenvironment conditions may lead to cancer cells becoming sensitized to subsequent therapy. This paper focuses on the therapeutic approaches modulating membrane antigens and enzymes in anticancer therapy. It aims to analyze the possible methods for modulating the antigens, such as pharmacological treatment, electric field treatment, photodynamic reaction, treatment with magnetic field or X-ray radiation. Besides, an overview of the effects of chemotherapy and immunotherapy on the immunophenotype of cancer cells is presented. Finally, the authors review the clinical trials that involved the modulation of cell immunophenotype in anticancer therapy.